2022
DOI: 10.3389/fbioe.2021.777648
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Validation of Venous Pulsatile Tinnitus and Biomaterial Applications for Temporal Bone Reconstruction Surgery Using Multi-sensing Platforms and Coupled Computational Techniques

Abstract: The application of grafts and biomaterials is a cardinal therapeutic procedure to resolve venous pulsatile tinnitus (PT) caused by temporal bone dehiscence during transtemporal reconstructive surgery. However, the transmission mechanism of venous PT remains unclear, and the sound absorption and insulation properties of different repair materials have not been specified. This study quantifies the vibroacoustic characteristics of PT, sources the major transmission pathway of PT, and verifies the therapeutic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…From the presence to the disappearance of PT, it is postulatsed that this quantitative range of flow velocity reduction offers a bottom-line curative marker for both extraluminal compression and endoluminal surgeries. However, the former surgical technique conceivably requires less flow velocity reduction due to the thickening of the soundproof sigmoid wall, although the compression depth of the transverse–sigmoid junction ought to be performed with circumspection to prevent the iatrogenic cause of intracranial pressure ( Hsieh et al, 2022 ; Qiu et al, 2022 ). A recent clinical study revealed that sinus flow velocity is reduced after a lumbar puncture without a concomitant reduction in the bulk flow rate, resulting in a 3.8 ± 3.4 improvement of PT intensity on a 0–10 Likert scale in 10 subjects ( Haraldsson et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the presence to the disappearance of PT, it is postulatsed that this quantitative range of flow velocity reduction offers a bottom-line curative marker for both extraluminal compression and endoluminal surgeries. However, the former surgical technique conceivably requires less flow velocity reduction due to the thickening of the soundproof sigmoid wall, although the compression depth of the transverse–sigmoid junction ought to be performed with circumspection to prevent the iatrogenic cause of intracranial pressure ( Hsieh et al, 2022 ; Qiu et al, 2022 ). A recent clinical study revealed that sinus flow velocity is reduced after a lumbar puncture without a concomitant reduction in the bulk flow rate, resulting in a 3.8 ± 3.4 improvement of PT intensity on a 0–10 Likert scale in 10 subjects ( Haraldsson et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous computational studies found that the flow-induced displacement of the vascular wall could generate vibro-acoustic noise from 48.76 to 116.57 dB ( Tian et al, 2017 ; Mu et al, 2021a , b ). The amplitude of the vibro-acoustic sound surpassed that of the hydroacoustic source when the volume and surface contributions were juxtaposed ( Hsieh et al, 2022 ). Nevertheless, based on intraoperative measurements, the frequency of vascular displacement was below the hearing threshold ( Hsieh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous computational studies, reducing the fluctuation of the flow velocity alleviates the wall pressure induced by the fluid-structure interaction and reduces the vibroacoustic component of PT. (6,15) Thus, if surgical reduction of the flow velocity is prioritized, the endoluminal stenting technique may be more suitable than the transtemporal technique since expanding the sinus lumen endoluminally is less likely to perniciously augment the intracranial pressure. (7,16,17) In contrast to transverse sinus stenting, using the transtemporal compression technique to reduce the flow velocity should prevent overcompressing the sinus lumen to avoid the iatrogenic cause of intracranial hypertension.…”
Section: Correlation Between Flow Amplitude and Flow Velocity Based O...mentioning
confidence: 99%
“…(9) Therefore, the degree of reduction of flow velocity and the patency of collateral sinuses should be carefully measured prior to surgical intervention. Since the surgical repair of dehiscence using robust biomaterials provides a therapeutic effect in alleviating PT, (15) the external compression technique can be performed as an additional or alternative method if addressing dehiscence alone fails to preclude PT. (10) Further studies on the range of velocity reduction and its surgical indication to eliminate PT are warranted.…”
Section: Correlation Between Flow Amplitude and Flow Velocity Based O...mentioning
confidence: 99%